Hybrid cultures, nervous states : Britain and Germany in a (post)colonial world - Lindner, Ulrike; Möhring, Maren; Stein, Mark, 1966-; Stroh, Silke (Cross/cultures, 2010)
While cultural diversity and hybridity have often been celebrated, they also challenge traditional concepts of national and cultural identity - challenges which have caused considerable anxiety. Various disciplines have often investigated the impact of cultural hybridity, multiculture, and (post)colonialism in relative isolation and with a tendency towards over-theorization and loss of specificity. Greater interdisciplinary cooperation can counter this tendency and encourage sustained comparisons between different former empires and across language boundaries. This volume contributes to such d.